Salinity tolerance of cumin (Cuminum cyminum L.) genotypes during germination - Jakhar, L S Dhayal, S C Bhargava, M L (Journal of Spices and Aromatic Crops, 2001)
A laboratory experiment was conducted to identify cumin (Cuminum cyminum L.) genotypes tolerant to salt at germination stage. Four salinity levels having electrical conductivity of 2.61 (control), 5.17 (low), S.10 (medium) and 12.15 (high) dSm-1 were tested. There is an increase in the suppression of seed germination with increase in salinity in all the genotypes tested. The genotype UC-20S showed maximum salt tolerance, followed by UC-209 and UC-2IS.